Efektivitas Program Rehabilitasi dan Rekonstruksi Pasca Bencana Banjir Bandang di Kabupaten Luwu Utara - Irma Wahyuni; Fuad Aziz; Tri Budiharto (Fakultas Teknik Universitas Bosowa, 2022)
This study aims to analyze the effectiveness of the rehabilitation and reconstruction program after the flash flood disaster in North Luwu Regency, to analyze the obstacles to the post-flood rehabilitation and reconstruction program in North Luwu Regency, as well as to identify the direction of recommendations in increasing the effectiveness of the post-flood rehabilitation and reconstruction program. Flash flood disaster in North Luwu Regency. This research uses a qualitative approach and a quantitative approach with the data collection process through observation, documentation and questionnaire surveys where the sample is drawn using the purpose sampling method. The data obtained were then analyzed using desctiptive and weighting. From the results of qualitative and quantitative analysis the effectiveness of the rehabilitation and reconstruction program was found, that the post-disaster rehabilitation program in North Luwu Regency was effective with an effectiveness score of 80,75 percent while the post-disaster reconstruction program in North Luwu Regency was categorized as quite effective with a score of 68,58 percent. From the effectiveness value, it is obtained that the constraints of the rehabilitation and reconstruction program are the need for funds for rehabilitation and reconstruction of infrastructure which is high so that direction is needed, namely the budget that has been estimated according to the damage to existing infrastructure is quickly realized on time.